A Study of EFL Students’ Learning Styles in English Classroom At SDN 5 Palembang - Eliza, Tiara (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2024)
The objective of this study is to identify the main types of learning styles of EFL students in SDN 5 Palembang. The unit of analysis of this study is EFL SDN 5 Palembang students studying at five levels. A qualitative approach was used to conduct this study: data was collected through observation and interview questionnaires. The study found that the learning styles of EFL students in English language instruction were kinesthetic, visual, auditory, and group-based. The results also showed that the most dominant learning style was kinesthetic. In other words, EFL students in SDN 5 Palembang preferred to learn English through a kinesthetic learning style.